O papel da gestão ambiental e das instituições bancárias no combate ao desmatamento na fronteira do sudeste do estado do Pará: apresentação do plano de mitigação para o município de Parauapebas no sudeste Do Pará - SOUZA, Juliana Fernanda Monteiro de (Universidade Federal do Pará, 2025)
The rural credit can be used as a mechanism for controlling and preserving the environment, through banking institutions, through responsible concessions to promote sustainable development, such as combating deforestation. From this perspective, the research aimed to investigate whether rural credit concessions, in the period from 2008 to 2020, have contributed to deforestation in the town of Parauapebas, in the southeast of the state of Pará. This is a basic, exploratory, correlational descriptive, action research, quantitative and qualitative. Regarding data collection procedures, the research carried out a bibliographic survey, documentary research and access to secondary data from public portals. This study also carried out field research, through meetings with interventions from the Municipal Group to Combat Illegal Deforestation (GCID) of Parauapebas. In relation to data analysis, geotechnology techniques were carried out to create cartography and statistical, descriptive and multiple regression analyses. The results demonstrated that the region showed persistent deforestation during the studied period, with the predominance of land use and occupation in rural areas for use as pastures. As found by the research in this dissertation, rural credit concessions in the period from 2008 to 2020 were predominantly for livestock farming activities, with 97.01% in relation to the total supported. Statistical analyzes demonstrated that rural credit promoted in the region is not a significant factor in deforestation rates, confirming the relevance of environmental management in financial institutions. The research also showed that the inclusion of environmental policies in banking institutions can contribute to the preservation of the environment, especially in this study, in the fight against illegal deforestation. Therefore, environmental regularization is mandatory for promoting rural credit. Finally, a product was developed, the Mitigation Plan, subsidized to contribute to establishing the goals of the Green Municipalities Program (GMP).